Remédios jurídicos contra a poluição plástica dos oceanos: uma análise dos esforços do direito internacional público e das iniciativas privadas para enfrentar a sopa de plástico - Gonçalves, Luísa Cortat Simonetti (2020)
The increasing amount of plastic being dumped into the oceans is alarming and has serious consequences, many of which are still unknown. It is estimated that at least 8 million tons end in the oceans annually and that, if the pace continues, by 2050 there will be more plastic than fish in the oceans (VALAVANIDIS; VLACHOGIANNI, 2014). Research already shows that we are eating (HAFFNER, 2009), drinking (CARRIGTON, 2017) and even breathing (VIANELLO, 2019) plastic. Furthermore, nature is suffering damages such as animal deaths due to starvation and entanglement, destruction of coral reefs, transport of invasive species (DE GUCHTE, 2005), and dispersion of toxic materials (HAFFNER, 2009). The legal field can contribute to a solution at different levels, such as national, regional and international, and from different perspectives on the problem. The thesis deals with the international context and questions how to build a mix between public and private initiatives to address the problem of plastic pollution in the oceans (or plastic soup), both to recover the plastic that is already there and to prevent more pollution between in the oceans. Four intermediate steps lead to the answer to the research problem. The first was to understand the current situation of plastic pollution in the oceans and what potential technical and technological solutions are being developed. The second was to clarify the importance of international action and to highlight aspects to avoid the common pitfalls of global north-south dynamics. The third was to analyze the eleven international instruments that are somehow related to the problem of plastic pollution. He showed that international law still does not provide convincing solutions. This, together with the fact that private companies are strong and directly linked to the problem, is the reason why the fourth step was to look at Corporate Social Responsibility (CSR) and other private initiatives, through four case studies. He concluded that none of the cases were successful in all effectiveness indicators. However, it also concluded on several positive aspects of these actions and on why companies would engage. The fifth step, then, was the end. I applied economic tools to analyze the previous conclusions, summarizing the lessons learned in two aspects that can guide an effective start in the construction of the mix and proposing an equation to apply the conclusions to the practical challenges.